The use of rodent models to investigate host–bacteria interactions related to periodontal diseases - Dana T. Graves, Daniel Fine (Blackwell Synergy, 2008)
Even though animal models have limitations, they are often superior to in vitro or clinical studies in addressing mechanistic questions and serve as an essential link between hypotheses and human patients. Periodontal disease can be viewed as a process that involves four major stages: bacterial colonization, invasion, induction of a destructive host response in connective tissue and a repair process that reduces the extent of tissue breakdown. Animal studies should be evaluated in terms of their capacity to test specific hypotheses rather than their fidelity to all aspects of periodontal disease initiation and progression. Thus, each of the models described below can be adapted to test discrete components of these four major steps, but not all of them. This review describes five different animal models that are appropriate for examining components of host–bacteria interactions that can lead to breakdown of hard and soft connective tissue or conditions that limit its repair as follows: the mouse calvarial model, murine oral gavage models with or without adoptive transfer of human lymphocytes, rat ligature model and rat Aggregatibacter actinomycetemcomitans feeding model.